A260 THE LACK OF CHROMOGRANIN-A MODIFIES THE GUT MICROBIOTA COMPOSITION AND REGULATES EXPERIMENTAL COLONIC INFLAMMATION - Eissa, N (J Can Assoc Gastroenterol, 2020)
BACKGROUND: Ulcerative colitis (UC)is characterized by distinct changes in the gut microbiome and elevated chromogranin-A (CHGA) level, which seem to be a relevant pathogenetic mechanism.CHGA, a prohormone produced by enterochromaffin (EC) cells and cleaved into several bioactive peptides, regulates experimental colonic inflammation. In the rodent, intra-rectal infusion of catestatin, a Chga-derived peptide, alters the distal colonic microbial composition. However, the interplay between CHGA, as a pro-hormone, and the gut microbiome remains elusive. AIMS: in homoeostatic and pathophysiologic conditions, we investigated the functional consequences of the lack of Chgaon the distal colonic microbiota. METHODS: Acute colitis (5 % dextran sulfate sodium [DSS], 5 days) was induced in Chga-C57BL/6-deficient (Chga(-/-)) and wild-type (Chga(+/+))mice. Feces and mucosa-associated microbiota (MAM) samples were collected and the V4 region of 16s rRNA was subjected to Miseq Illumina sequencing. Alpha diversity was calculated using Shannon’s diversity index. OTU abundances were summarized using the Bray-Curtis index and non-metric multidimensional scaling (NMDS) analysis to visualize microbiome similarities and a permutational analysis of variance (PERMANOVA) to test the significance of groups were performed respectively. RESULTS: In non-colitic homoeostatic condition, the absence of Chga (Chga(-/)) significantly increased the bacterial richness and modified the bacterial community composition at the genera level between the groups, represented by increased abundance of Lactobacillus species and reduced abundance of Helicobacter& Oscillospira species compared to Chga(+/+)mice in fecal and colonic MAM. Moreover, the absence of Chga (Chga(-/-)) resulted in a significant change in the alpha-diversity of fecal and colonic MAM compared to Chga(+/+)mice. DSS induced-colitis resulted in a significant microbial dysbiosis in Chga(+/+)mice, however, deletion of Chgaprotected against DSS-induced colitis and reduced the microbial dysbiosis, reduced the family of Rikenellaceaeand maintained the abundance of Bacteroides species, compared to wild-type (Chga(+/+)). CONCLUSIONS: The lack of CHGA regulates the biodiversity and the composition of the colonic gut microbiota suggesting a cross-talk between the EC cell and the microbiome. Therefore, targeting CHGA could provide a novel therapeutic strategy by regulating the gut microbiome in physiological and pathophysiological conditions. FUNDING AGENCIES: CIHR